2003
DOI: 10.1002/jcp.10344
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensing role of caveolae and caveolar constituents in human endothelial cells

Abstract: A variety of evidence suggests that endothelial cell functions are impaired in altered gravity conditions. Nevertheless, the effects of hypergravity on endothelial cell physiology remain unclear. In this study we cultured primary human endothelial cells under mild hypergravity conditions for 24-48 h, then we evaluated the changes in cell cycle progression, caveolin1 gene expression and in the caveolae status by confocal microscopy. Moreover, we analyzed the activity of enzymes known to be resident in caveolae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 37 publications
6
49
0
Order By: Relevance
“…Indeed, exposure to 3g hypergravity for 4 h already resulted in a slight reduction (although not significant) of the number of capillarylike structures formed, in comparison to the 1g control. The same tendency was observed for a longer exposure period, with HUVECs exhibiting a diminished ability to organize into capillary-like structures after being cultured at 3g for 16 h. Accordingly, Spinsi et al reported inhibition of the angiogenic behaviour of HUVECs cultured in a three-dimensional collagen gel and exposed to 3g hypergravity for 48 h [33]. Despite the fact that no quantification is presented by the authors, results from this work showed that the formation of capillary-like structures was strongly impaired after culturing cells in a three-dimensional collagen gel at 3g with the addition of basic fibroblast growth factor [33].…”
Section: In Vitro Angiogenesis Under Hypergravitymentioning
confidence: 61%
“…Indeed, exposure to 3g hypergravity for 4 h already resulted in a slight reduction (although not significant) of the number of capillarylike structures formed, in comparison to the 1g control. The same tendency was observed for a longer exposure period, with HUVECs exhibiting a diminished ability to organize into capillary-like structures after being cultured at 3g for 16 h. Accordingly, Spinsi et al reported inhibition of the angiogenic behaviour of HUVECs cultured in a three-dimensional collagen gel and exposed to 3g hypergravity for 48 h [33]. Despite the fact that no quantification is presented by the authors, results from this work showed that the formation of capillary-like structures was strongly impaired after culturing cells in a three-dimensional collagen gel at 3g with the addition of basic fibroblast growth factor [33].…”
Section: In Vitro Angiogenesis Under Hypergravitymentioning
confidence: 61%
“…35,36 This effect is specific for COX-2; in fact, COX-1 was mainly localized in the cytoplasm and was not modulated by HDL 3 ; moreover, PGI 2 synthesis was downregulated by a specific COX-2 inhibitor.…”
Section: Discussionmentioning
confidence: 92%
“…PGI-S resides in caveolae in resting cells. 33 Caveolin-1 is the main protein of caveolae, and when phosphorylated 34 it moves into the cytoplasm, 34,35 shuttling PGI-S in the perinuclear area where it couples to COX-2, 35 thus increasing prostacyclin synthesis. We investigated, therefore, whether HDL can influence caveolin-1 phosphorylation and shuttling in the perinuclear space.…”
mentioning
confidence: 99%
“…Cyclooxygenase-2 enzymatic activity was evaluated by measuring the 6-keto-PGF1a release in conditioned media by using an ELISA assay (Assay Designs, USA), as previously described (Spisni et al, 2003). 6-ketoPGF1a production was then related to the protein concentration in cell lysates.…”
Section: Determination Of Cox-2 Activitymentioning
confidence: 99%
“…In vitro angiogenesis was evaluated by seeding HUVE cells on a 3-D collagen gel in a 24-well plate, as previously described (Spisni et al, 2003), and transfecting them with siRNAs. Briefly, collagen gel was prepared by adding eight volumes of collagen solution (3 mg ml À1 , Roche Applied Science, USA) to two volumes of a mixture containing M199 5 Â , HEPES 0.02 M and NaHCO 3 7.5 mg ml À1 .…”
Section: In Vitro Angiogenesis Testmentioning
confidence: 99%